Structural Integrity Of Composite Laminates Panel Using Ultrasound Technique - Duasing, Joshua Boniface (Universiti Sains Malaysia, 2018)
Advancement of technology made possible the change in utilization of material in the industry especially in aerospace industry. Fiber-reinforced laminated composite are now widely used in aircraft as well as modern vehicle. Comparing to other conventional traditional structural material, composite has high elastic modulus as well as high strength to weight ratio in addition to their wide usage. However, their behavior under impact is still a concern as it may face those event across its entire life span from manufacturing, during service or even in maintenance. This is vital as low-velocity impact can induce internal damage while not noticeable by visual inspection. Ultrasound technique provides a clear answer where a non-destructive test could be carried out to examine the inside of a structure. The test piece are subjected to drop impact test to simulate real world situation. Ultrasound scanning is done before and after the impact test. A good correlation between the impact energy and the maximum peak reading for ultrasound is noticed. This study provides a better understanding about ultrasound technique and why it is important for future structural assessment.